Dinamika Daya Saing Lada Indonesia - Sri Hery Susilowati (Jurnal Agro Ekonomi, 2003)
EnglishIndonesia is  one of the major producer contries of pepper (Piper Nigrum L) along with India, Brazil and Malaysia.  With the increase of  market competition among  them in international  market, Indonesia has to be able to increase  market  competitiveness of pepper exports againts  competitors.   The purpose of this study is to analize the competitiveness of  Indonesia pepper exports among the competitors in international market.  Time series data of 1985 – 2001 were  used and most the data came from  the International Pepper Statistic  Year Book. The results of analysis showed that for  all  analysis periodes,  Indonesia  exports competitiveness has increased  to three other  competitors, except for the first   periode (1985-1996),  which  India and Malaysia competitiveness is higher than  Indonesia. Market distribution effect showed that  USA,  MEE and Singapore markets are proper market for Indonesia pepper export. IndonesianDiantara negara-negara produsen lada dunia, Indonesia termasuk salah satu produsen utama dunia bersama-sama dengan India, Malaysia dan Brazil. Dengan meningkatnya kompetisi antara negara produsen, Indonesia dituntut untuk mampu mempertahankan daya saingnya di pasar internasional. Kajian ini bertujuan untuk menelaah posisi daya saing ekspor Indonesia relatif terhadap beberapa negara pesaingnya  di pasar lada dunia.  Data yang digunakan adalah data deret waktu periode 1985-2001 yang bersumber dari International Pepper Community Statistical Year Book. Dari hasil analisis dapat ditunjukkan bahwa untuk seluruh periode analisis, daya saing Indonesia mengalami peningkatan relatif terhadap tiga negara pesaingnya, kecuali pada periode awal (1985-1996) dimana daya saing India dan Malaysia mengungguli Indonesia. Pengaruh distribusi pasar menunjukkan bahwa pasar Amerika Serikat, MEE dan Singapore merupakan pasar tujuan yang tepat bagi ekspor lada Indonesia.